Population structure of yellowtail snapper using age-based life history and otolith shape in southern Gulf of México - Ximena Renán; Gabriela Galindo-Cortes; Isabel Cervantes-Camacho; Mariana Ramírez; Marco A. Pasos; Teresa Colás-Marrufo; Thierry Brulé (PLoS ONE, 2025)
Yellowtail snapper Ocyurus chrysurus is commercially important throughout its distribution range. In southern Gulf of México, it is caught as part of a largely undocumented multispecific snapper fishery. Samplings were done at three fishing sites with the highest landings volume of Yucatán, México: Celestún, Dzilam de Bravo, and Río Lagartos. Age and growth parameters were generated with the von Bertalanffy growth model via annuli counts in otolith thin sections of 1,124 individuals. Marginal increment analysis confirmed that opaque zone formation is annual and occurs from July to September. Overall age range was 0 + to 12 years (17.7 to 38.9 cm fork length) but differed between Celestún (0 + to 9 years), Dzilam de Bravo (1 to 12 years), and Río Lagartos (2 to 12 years). Growth parameters and lifespan for combined sexes also varied between sites: Celestún (L ∞ =  41.59 cm, K =  0.11 year-1, tmax =  22.41 years); Dzilam de Bravo (L ∞ =  38.36 cm, K =  0.16 year-1, tmax = 15.5 years); and Río Lagartos (L ∞ =  40.28 cm, K =  0.12 year-1, tmax =  20.01 years). Age at maturity was 1.3 years for females and < 1 year for males. Natural mortality based on tmax was 0.28 year-1 overall. A principal coordinates analysis identified morphometric variables as explaining 92.2% of otolith differentiation by fishing site, with average centroid distances: Celestún, 1.98; Dzilam de Bravo, 2.22; and Río Lagartos, 2.75. Differences in growth rate, lifespan, natural mortality and otolith shape indicate that O. chrysurus in southern GoM exhibits structural complexities that suggest the occurrence of repercussions from fishing-induced demographic changes.